An assessment of Geotem, Falcon® and ZTEM surveys over the Nebo Babel deposit, Western Australia. Issue 1 (1st December 2018) - Witherly, Ken; Sattel, Daniel
Abstract : The Nebo Babel Ni-Cu deposit was discovered in 2000 by Western Mining Corporation (WMC). BHP acquired WMC in 2005 and advanced the project. In 2014, BHP optioned the property to Cassini Resources and in 2016 Cassini partnered with Oz Minerals to further advance the project. During the period when WMC and BHP held the project, extensive airborne geophysical investigations were conducted including Geotem, Falcon ®, ZTEM, AirMt and Spectrem. Parts of the mineralized system respond well to the various airborne EM techniques but the response overall is complicated by the presence of extensive paleochannel development. A combination of 1D, 2D and 3D processing techniques have been applied to the EM data so as to better understand the overall system responses and where possible, see if it were possible to separate the basement conductive response from that of the overlying Tertiary channels.